Approximating Nonlinear Relations Between Susceptibility andMagnetic Contents in Rocks Using Neural Networks - Guo, W.; Li, M.; Li, Zhengxiang; Whymark, G. (Elsevier Science BV, 2010)
Correlations between magnetic susceptibility and contents of magnetic minerals in rocks are importantin interpreting magnetic anomalies in geophysical exploration and understanding magnetic behaviorsof rocks in rock magnetism studies. Previous studies were focused on describing such correlations using a sole expression or a set of expressions through statistical analysis. In this paper, we use neural network techniques to approximate the nonlinear relations between susceptibility and magnetite and/or hematite contents in rocks. This is the first time that neural networks are used for such study in rock magnetism and magnetic petrophysics. Three multilayer perceptrons are trained for producing the best possible estimation on susceptibility based on magnetic contents. These trained models are capable of producing accurate mappings between susceptibility and magnetite and/or hematite contents in rocks. This approach opens a new way of quantitative simulation using neural networks in rock magnetism and petrophysical research and applications.